Atividades de estimulação do desenvolvimento na educação infantil: estudo sobre indicadores de viabilidade na perspectiva de professores - Sousa, André Luiz de [UNIFESP] (2019)
Currently, studies seek to implement interventions, programs, policies or products aimed at early childhood care, based on scientific evidence. The present study was developed in the context of a broader study oriented to the development of a program of stimulation of cognitive and social emotional development associated with pedagogical practice, based on the model of early intervention, Pre-K RTI (Preschool Response to Intervention). The objective was to analyze feasibility and applicability indicators of a program support material with activities to stimulate child development for early childhood education, compiled in four booklets, in two phases. In the first phase, the suitability of the activities was analyzed from a sample of 12 nursery school teachers and four judges specializing in developmental neuropsychology, through forms. The data were analyzed qualitatively and the analysis resulted in the reformulation of the booklets, generating a final version. In the second phase, a pilot study on feasibility and applicability indicators was carried out from the perspective of eight pre-school teachers. A socio-demographic questionnaire was used, with questions about the knowledge of the themes of the booklets, and a registration form for the use of the activities. The data were analyzed qualitatively based on four viability criteria according to the international literature: acceptability, demand, implementation and practicality. There was a relative low adherence of teachers to the use of daily activities, and most of the activities used were related to motor and language development. These observations indicate the need to expand research in order to promote the implementation of activities to stimulate child development based on indicators of feasibility and applicability